SISTEM INFORMASI GEOGRAFIS PEMETAAN PENYEBARAN PERTASHOP DI WILAYAH KABUPATEN PIDIE BERBASIS WEBGIS - Nashrudin; Qadriah, Laila; Salat, Junaidi (Sagita Academia Journal, 2024)
Pertashop is a small distribution agent that serves consumers at the village level far from gas stations. In addition to the General Fuel Filling Station (SPBU), PT Pertamina (Persero) also operates a Pertamina Shop (Pertashop) for purchasing fuel oil (BBM). Pertashop was created to reach areas that are considered far from gas stations. The product being sold is the Pertamax type of fuel, then there is LPG, namely Bright Gas. Pertashop is a sort of channeling institution at the village level. This expands people's access to energy. This means that people who live far from gas stations can use the pertashop that is present at the village level. The problem is that not all of the people, especially immigrants, know the location of the Pertashop location when the situation is urgent, especially the immigrant community. The presence of Pertashop competes with gas stations. The existence of this pertashop is to bring BBM services closer on a small scale to the community, especially those in remote villages or in the interior of the mountains. Besides that, Pertashop is the best choice when the vehicle runs out of fuel. Therefore, based on the problems above, the researcher wishes to overcome these problems in the form of a final project with the title "Geographical Information System for Mapping the Distribution of Pertashop in the Pidie District Based on WebGIS". Hopefully with this system it can help make it easier for the community to find out the location of Pertashop in Pidie Regency.